Igneous Rock Associations 1. Styles and Mechanisms of Caldera Collapse - Kennedy, Ben; Stix, John (Geoscience Canada, 2003)
In this article, we summarize some of the most influential papers and concepts regarding caldera collapse. We also present a synopsis of the different types of calderas, their characteristics and field examples and provide a glossary of related nomenclature. We discuss piston, downsag, trapdoor, concentric step-down, chaotic, rifted and piecemeal calderas. Some calderas appear to be combinations of different types. We examine the complex interactions of variables that control the structure and morphology of calderas and result in a particular collapse style. Sommaire Le présent article fait état des concepts et des publications les plus importantes en matiPre d’effondrement des caldeiras. On y présente également une vue d’ensemble des différents types de caldeira, leurs caractéristiques illustrées d’exemples concrets, ainsi qu’un glossaire de la nomenclature afférente. Nous traiterons des concepts de piston, d’affaissement, d’effondrement concentrique par paliers, ainsi que de caldeiras de style chaotique, de fossé tectonique et fragmentaire. Il semblent que certaines caldeiras soient le résultat d’une combinaison de style. Nous considérons les interactions complexes de variables qui déterminent la structure et la morphologie des caldeiras et en conditionnent le style.